Genética del cáncer del colon - Passalacqua H., Cristóbal; Aravena C., Teresa; Silvia Castillo T., Silvia Castillo T. (Revista Hospital Clínico Universidad de Chile, 2010)
Colon cancer (CC) is a prevalent disease, with 800,000 new cases annually worldwide. In Chile the mortality is 6.2 per 100,000 inhabitants, which has increased in recent years, being more common in developed countries. Although, CC are most sporadic forms (70%), there are patients with family history (30%) and 10% have a hereditary component, with a predisposition to the formation of tumors, including CC, the most studied syndrome are: Familial Adenomatous Polyposis (FAP), Peutz-Jeghers syndrome and hereditary non-polyposis colon cancer (HNPCC). The progresses made by the human genome sequencing have allowed to known mutations in oncogenes and tumor suppressor genes that occur in a cell of the normal intestinal mucosa and lead to carcinogenic transformation. This review is an update of the known genes related to the sporadic form of the CC, as well as the most common inherited forms of CC. It is important that health professionals, be aware of developments in this area, because they are who should promote in the community a timely screening for patients with increased risk factors for CC, with the aim of giving an accurate counseling for decrease the morbidity and mortality of this condition.